Spending Estimates for Gastric Cancer in Central Brazil (Brazilian Journal of Pharmaceutical Sciences, 2022)
Stomach cancer is the second leading cause of death by cancer worldwide and is even more pronounced in South America. In Brazil, it is estimated that an increase in the number of cases due to this cancer occurred in the biennium 2018-2019. In this study, we investigated the expenditures of the State Health Department of Goiás on hospitalizations and treatment of gastric cancer for the Unified Health System (SUS) from 2008-2016. This is a cross-sectional, descriptive, and analytical study based on secondary data from the Unified Health System computing department (DATASUS) and the System of Management of the Table of Procedures, Medications, Orthosis, Prosthesis, and Special Materials of SUS through CONECTA-SUS related to International Classification of Diseases-10/C16 (ICD-10/C16) procedures for gastric neoplasms. A total of I$ 5,697,958.20 was spent on gastric tumor in the last nine years in Goiás, I$ 4,492,916.67 (0.3%) on hospitalizations, and I$ 1,997,120.91 on treatment. This study presents a current and relevant estimate of the costs of gastric cancer patients in Goiás. Moreover, we provide information on the extent of the cancer issue to public health. Our analysis offers components for service management and studies that reduce resource allocation in more rational ways.